FEATURES OF DEVELOPMENT AND APPLICATION OF AEROBICS IN THE SYSTEM OF PHYSICAL EDUCATION - Shuba Liudmyla; Shuba Victor; Shuba Victoria (Alfred Nobel University Publisher, 2024)
The article examines the impact of aerobics and physical education programs including aerobics on the physical and mental health of the younger generation. The purpose of the study is to analyse the peculiarities of using aerobics in different countries of the world and to identify the positive/negative aspects of physical activity. The article employs methods of retrospective and comparative analysis of primary sources, as well as generalization and systematization of innovative points regarding the integration of aerobics into educational programs. It has been stated that aerobics is a universal form of physical activity that can be adapted to the needs of each person, regardless of gender. Today, aerobics is a popular form of fitness that includes a variety of training styles and methods, from classic group classes to modern interactive online training. It not only helps to strengthen the cardiovascular system, but also enhances the general tone of the body and improves mood. To get the most out of training, it is important to consider individual physiological characteristics and goals. Aerobics has been increasingly integrated into physical education programs in various countries such as Great Britain, Australia, the United States of America, China, the Philippines, and South Korea. Integrating aerobics into a physical education program helps develop discipline and self-discipline, as well as promotes a healthy and active lifestyle among the growing generation, giving them the tools to stay fit throughout life. Regular physical activity, including aerobic exercise, can improve cognitive function and concentration, which has a positive effect on the academic achievement of young people. Positive aspects are as follows: improvement of cardiovascular health; improvement of mood and mental health; weight control due to assistance in burning calories, which helps maintain a healthy weight and prevent obesity; improving physical shape, increasing endurance and strengthening muscles; formation of discipline; improvement of cognitive functions; promoting socialization, helping to make new friends and gaining support from like-minded people in group aerobics. Meanwhile, certain negative consequences that may arise from improper organization of aerobics classes have been identified, including the risk of injury, overloading the cardiovascular system, the necessity of adhering to proper technique, and psychological stress. The characteristic features of modern health aerobics are: accessibility and ease of performing exercises; increased emotionality of classes due to musical accompaniment and different movements; high effectiveness of the health-improving effect due to the continuity of physical exercises aimed at the development of general endurance, flexibility and strength, as well as improving the work of the cardiovascular, respiratory systems and musculoskeletal system; a high level of scientific substantiation of training methods, constant development of the material and technical base and development of new types of equipment for aerobics. Quality of life and level of well-being mainly depend on a person's ability to live fully and actively, unencumbered by health problems. That is why, nowadays, aerobic exercises are becoming more and more popular, as they contribute to health and general strengthening of the body. Conclusion. A comparative analysis of the role and significance of aerobics in the physical education systems of developed countries highlights the importance of integrating physical activity into the curriculum for the overall health and well-being of the younger generation.